Field evaluation of a quantitative polymerase chain reaction assay for Mycoplasma hyorhinis. (November 2014) - Clavijo, Maria J.; Oliveira, Simone; Zimmerman, Jeffrey; Rendahl, Aaron; Rovira, Albert
Mycoplasma hyorhinis has emerged as an important cause of systemic disease in nursery pigs. However, this bacterium can also be found in the upper respiratory tract of healthy swine. The current study describes the development of a quantitative polymerase chain reaction assay for the detection of M. hyorhinis and the evaluation of the assay in both disease diagnosis and disease surveillance using a large number of field samples. The analytical sensitivity was estimated to be 12 genome equivalents/μl. The assay was highly specific, detecting all 25 M. hyorhinis isolates tested and none of the 19 nontarget species tested. Assay repeatability was evaluated by testing different matrices spiked with known amounts of M. hyorhinis . Overall, assessment of the repeatability of the assay showed suitable precision within and between runs for all matrices. The coefficient of variation ranged from 10% to 24%. Mycoplasma hyorhinis DNA was detected in 48% of samples (pericardium, pleura, joints, nasal cavity, and lungs) from pigs with systemic disease. Mycoplasma hyorhinis was detected in nasal (92%) and oropharyngeal swabs (66%), as well as in oral fluids (100%). Potential uses of this tool involve the characterization of the prevalence of this pathogen in swine herds as well as bacterial quantification to evaluate intervention efficacy.